Pendampingan Awal Literasi Membaca dan Pembuatan Pojok Baca pada Anak-Anak Usia Dini di Desa Kebonsawahan Juwana Pati Jawa Tengah - Chasannudin, Arif; Malikah, Hanik; Laily, Aizzah; Bastomi, Ahmad (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2024)
Literacy is the ability to read, write and speak, which requires knowledge of genre and culture. Ironically, Indonesia is among the countries with low literacy levels according to PISA research. Therefore, it is necessary to have a massive literacy culture from an early age. This community service activity uses the ABCD (Asset Based Community Development) method to develop a community based on educational assets. This ABCD method uses 5 (five) steps, namely discovery, dream, design, define and destiny. This community service activity was carried out based on the need to improve literacy culture from an early age. This activity was carried out by creating a reading corner at KB Hamerti Siwi, Kebonsawahan Village, Juwana District, Central Java Regency. A reading corner is a corner of the classroom equipped with bookshelves and a collection of interesting books for children. The book corner can act as an extension of the library function to increase students' interest in learning to read. The activity was carried out from July 10 to August 20, 2024. The result of this activity is the establishment of a reading corner space that can be utilized by students to get to know reading, as well as literacy assistance to students in utilizing the reading corner.